2018
DOI: 10.1002/jms.4288
|View full text |Cite
|
Sign up to set email alerts
|

Application of proton transfer reaction mass spectrometry for the assessment of toluene removal in a nonthermal plasma reactor

Abstract: Proton transfer reaction mass spectrometry (PTR-MS) is a mature technique for the real-time measurement and monitoring of volatile organic compounds in the atmosphere. In this paper, a modified quantification method for PTR-MS was used to assess the performance of nonthermal plasma (NTP) reactor for the removal of toluene which was widely used in industrial production processes. Toluene and 11 corresponding organic by-products were tentatively identified and quantified by a proton transfer reaction time-of-fli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
(76 reference statements)
1
3
0
Order By: Relevance
“…The change in the discharge voltage was exactly the same for all three VOCs; however, the discharge current was slightly different, which resulted in the shift of the data points for the three curves along the horizontal axis. As shown in figure3(a), the degradation rate of these three VOCs increases proportionally with the increase in SIE, which is similar to the pattern reported in[46][47][48]. The degradation rate of TOL was significantly higher than that of EA and AC.…”
supporting
confidence: 83%
“…The change in the discharge voltage was exactly the same for all three VOCs; however, the discharge current was slightly different, which resulted in the shift of the data points for the three curves along the horizontal axis. As shown in figure3(a), the degradation rate of these three VOCs increases proportionally with the increase in SIE, which is similar to the pattern reported in[46][47][48]. The degradation rate of TOL was significantly higher than that of EA and AC.…”
supporting
confidence: 83%
“…The structure of the DBD reactor that was introduced in our previous work (Guo et al 2018b) is shown in Fig. 2.…”
Section: Dbd Reactormentioning
confidence: 99%
“…The plasma was generated by a high-voltage power supply (CTP-2000k, Nanjing Moersi Electronics Co., Ltd., China), and its electrical characterization was monitored by a digital storage oscilloscope (DSO7052A, Agilent, USA). The discharge power (p) is calculated by multiplying the area of the charge-voltage Lissajous figure S by the frequency f (Guo et al 2018b;Jiang et al 2013)…”
Section: Dbd Reactormentioning
confidence: 99%
See 1 more Smart Citation